2021
DOI: 10.3390/antiox10050689
|View full text |Cite
|
Sign up to set email alerts
|

Virgin Olive Oil Phenols, Fatty Acid Composition and Sensory Profile: Can Cultivar Overpower Environmental and Ripening Effect?

Abstract: The authenticity and typicity of monocultivar oils and knowledge of the changes that environmental olive growing conditions bring to naturally present antioxidants and sensory attributes of virgin olive oils (VOO) are important for quality and safety improvement. This study delivers a comprehensive evaluation of the factors affecting phenolics, fatty acid composition and sensory characteristics of cultivars Oblica and Leccino VOOs throughout ripening season at two distinct olive growing environments during thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 74 publications
(92 reference statements)
5
33
0
Order By: Relevance
“…Oils from Lastovka and Levantinka had similar values for TPC. The mean TPC value in Oblica oil (438.3 mg/kg) were in concordance with the data obtained in the study of Jukić Špika et al [39] for the same crop year, but still lower compared with another study of Lukić et al [59] during the crop year of 2015, where the fruit ripening showed the strongest effect on the accumulation of phenolic compounds. Levantinka oils had a mean TPC value (302.1 mg/kg) higher than the detected value for this monovarietal oil in a previous study [61].…”
Section: Voo Quality Assessmentsupporting
confidence: 90%
See 4 more Smart Citations
“…Oils from Lastovka and Levantinka had similar values for TPC. The mean TPC value in Oblica oil (438.3 mg/kg) were in concordance with the data obtained in the study of Jukić Špika et al [39] for the same crop year, but still lower compared with another study of Lukić et al [59] during the crop year of 2015, where the fruit ripening showed the strongest effect on the accumulation of phenolic compounds. Levantinka oils had a mean TPC value (302.1 mg/kg) higher than the detected value for this monovarietal oil in a previous study [61].…”
Section: Voo Quality Assessmentsupporting
confidence: 90%
“…In Oblica VOOs, the mean value of C18:2 was 9.66%, followed by Levantinka with 6.78%, while the significantly lowest content of linoleic fatty acid was detected in Krvavica olive oils (4.62%). In comparison with data from another study [39], Oblica had a high C16:0 content (average 13.43%) as well as a medium content of C18:2 (average 11.22%). C18:2 content in the Leccino cultivar grown in Croatia [39] was of an average of 6.99%…”
Section: Fatty Acid Compositionmentioning
confidence: 54%
See 3 more Smart Citations